Test of Phytocemical Levels of Bidara (Ziziphus spina-christi L.) Potential as Medicinal Plants - Yetti Hastiana; Sapta Handaiyani; Icke Agustin (Universitas Wiralodra, 2022)
Arabic bidara or Ziziphus spina-christi L. is a plant that has potential in the traditiobal medicine industry. Based on research reports on bidara leves (Ziziphus spina-christi L.) can be useful as antioxidants, anti-inflammatory, antimicrobial, antifungal and prevent tumors. Bidara leaves (Ziziphus spina-christi L.) contain secondary metabolites that have many health benefits, secondary metabolites include flavonoids, alkaloid, saponins, steroids and tannins. The pupose of this study: To determine the levels of phytochemicals in the leavels of the bidara Arabic plants (Ziziphus spina-christi L.) as a medicinal plant. According to Mulyatiningsih (2011) this research uses a quantitative descriptive method. Based on the results of the study, the levels of the bidara leaf (Ziziphus spina-christi L.) produced varying levels of secondary metabolites, namely alkaloid, flavonoids, saponins, steroids and tannins. The average levels of secondary metabolites, including flavonoids, produced levels of 3.030%, alkaloids produced levels of 23.537% saponins produced levels of 5.5307, tannis produced levels of 0.0933% and steroid produced levels of 3.494%. of the five compounds, the highest compounds that have the potential as medicinal plants are alkaloid compounds that produce levels as much as 23.537%, and the lowest compounds, namely tannins, produce levels of 0.0933%. The hope in the future from the compounds that have been studied is that they are used as herbal medicines by the community and as references for for other researchers.